The Effect of Entrepreneurial Orientation on Organizational Resilience Through Entrepreneurial Bricolage Study on Small Businesses of IWAPI Members in Banten Province - Erna Maulina; Reza Damayanti (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to examine the effect of entrepreneurial orientation (EO) on organizational resilience (OR) through entrepreneurial bricolage (EB) among women-owned small enterprises that are members of IWAPI in Banten Province. The research addresses the issue of how entrepreneurial values and resource improvisation strengthen the adaptability and sustainability of small businesses operated by women entrepreneurs in a dynamic business environment. The study employs a quantitative approach using the Partial Least Squares–Structural Equation Modeling (SEM-PLS) method to analyze data collected from members of IWAPI Banten. The variables measured include entrepreneurial orientation, entrepreneurial bricolage, team governance, and organizational resilience. The analysis examines both direct and indirect effects to identify mediation mechanisms.The results show that EO has a positive and significant effect on both EB and OR. EB also positively influences OR and significantly mediates the relationship between EO and OR, indicating that entrepreneurial creativity and resource improvisation enhance organizational resilience. However, EB does not significantly mediate the effect of team governance on OR, suggesting that governance impacts resilience more directly through coordination and team effectiveness.The findings highlight that entrepreneurial orientation and adaptive resource management through bricolage are key drivers of organizational resilience in women-led small enterprises